Potential mammary carcinogens used in food contact articles: implications for policy, enforcement, and prevention - Parkinson, Lindsey V.; Geueke, Birgit; Muncke, Jane (Frontiers in Toxicology, 2024)
Many nations have food contact material (FCM) legislation purporting to protect citizens from hazardous chemicals, often specifically by regulating genotoxic carcinogens. Despite such regulations, cancers that are associated with harmful chemical exposures are highly prevalent, especially breast cancer. Using the novel Key Characteristics of Toxicants framework, Kay et al. found 921 substances that are potential mammary carcinogens. By comparing Kay et al.‘s chemicals list with our own Database on migrating and extractable food contact chemicals (FCCmigex), we found that 189 (21%) of the potential mammary carcinogens have been measured in FCMs. When limiting these results to migration studies published in 2020–2022, 76 potential mammary carcinogens have been detected to migrate from FCMs sold in markets across the globe, under realistic conditions of use. This implies that chronic exposure of the entire population to potential mammary carcinogens from FCMs is the norm and highlights an important, but currently underappreciated opportunity for prevention. Reducing population-wide exposure to potential mammary carcinogens can be achieved by science-based policy amendments addressing the assessment and management of food contact chemicals.